2017
DOI: 10.1186/s13613-017-0255-8
|View full text |Cite
|
Sign up to set email alerts
|

Systematic overdosing of oxa- and cloxacillin in severe infections treated in ICU: risk factors and side effects

Abstract: BackgroundOxacillin and cloxacillin are the most frequently used penicillins for the treatment of severe methicillin-susceptible Staphylococcus aureus infections in intensive care units (ICUs), especially endocarditis. International recommendations do not suggest any adaptation of the dosage in case of renal impairment. We wanted to assess the risk factors for overdosing in ICU and the related observed side effects.MethodsAll patients with a therapeutic drug monitoring of oxa- or cloxacillin between 2008 and 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(16 citation statements)
references
References 39 publications
1
15
0
Order By: Relevance
“…We found that, despite patients were prescribed the cloxacillin dose recommended by guidelines, taking into account their eGFR, 57% had trough plasma concentration > 50 µg/mL. This result is consistent with a recent study that reported trough plasma concentration > 50 µg/mL in 83.9% of 62 patients treated by oxacillin or cloxacillin in intensive care unit [6]. Of note, intravenous cloxacillin is mainly bound to plasma proteins (>90%) [23], and the active metabolite is the unbound fraction.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
See 1 more Smart Citation
“…We found that, despite patients were prescribed the cloxacillin dose recommended by guidelines, taking into account their eGFR, 57% had trough plasma concentration > 50 µg/mL. This result is consistent with a recent study that reported trough plasma concentration > 50 µg/mL in 83.9% of 62 patients treated by oxacillin or cloxacillin in intensive care unit [6]. Of note, intravenous cloxacillin is mainly bound to plasma proteins (>90%) [23], and the active metabolite is the unbound fraction.…”
Section: Accepted Manuscriptsupporting
confidence: 91%
“…Cloxacillin plasma concentration was determined by high-performance liquid chromatography method with UV detection, as previously described [5]. The target range of trough concentration (or steady-state concentration, in case of continuous administration), was 20-50 µg/mL, as previously described [6].…”
Section: Clinical and Biological Datamentioning
confidence: 99%
“…Delirium is multifactorial and frequent in critically ill ICU patients [ 6 , 27 35 ]. It is diagnosed in 10–90% of ICU patients, depending on the diagnosis tool, the timing of assessment (during or after interrupting sedation), as well as the frequency of assessment (one-point assessment for validation studies or throughout the ICU stay) [ 6 , 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…Even in such an “a priori” favorable setting for the early recognition of delirium, bedside–clinicians still need to use a validated tool during their routine practice, repeatedly during the day and throughout the ICU stay. This is paramount for treating the factors associated with delirium [ 6 , 27 35 ] as soon as possible, especially when taking into account the negative outcomes associated with delirium [ 5 , 6 ]. A comprehensive approach [ 48 ] integrating delirium management with analgesia, sedation, mechanical ventilation, mobility/exercise and family engagement/empowerment has shown a positive impact on increasing ventilatory-free days [ 49 , 50 ], decreasing delirium incidence [ 49 51 ] and improving hospital mortality [ 51 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the pathophysiology of delirium remains poorly understood, we know that the pathogenesis of the cognitive impairments associated with delirium is multifactorial. Certain entities such as drug overdose [16] but also drug withdrawal [17] bear delirium risk. As with so many disparate etiologies, it is highly unlikely that a single mechanism is solely responsible [18].…”
Section: Introductionmentioning
confidence: 99%